Pelatihan Program Kreatifitas Mahasiswa (PKM) untuk Meningkatkan Minat dan Motivasi Mahasiswa - Meyliana Chandra; Listya Sya’bani; Jihan Rahayuningsih; Moia Pravayangastha; Marsha Aulia Azahra; Arief Nurrahman (Universitas Kristen Indonesia Toraja, 2025)
The Student Creativity Program (PKM) is an initiative by the Directorate General of Higher Education aimed at enhancing students' creativity and skills in facing global challenges. The PKM training by the service team is aimed at enhancing the understanding and abilities of FEB UNY Accounting Education students in systematically and relevantly preparing PKM proposals. This program is designed to help students overcome obstacles in determining appropriate PKM ideas and titles, as well as providing technical guidance in preparing competitive proposals. The training used methods such as needs analysis, planning, material presentation, interactive discussions through Focus Group Discussions (FGD), as well as evaluation and analysis of the activity results. The training results show that 48% of participants are interested in the PKM-K field, 45% in PKM-PM, 3% in PKM-RSH, and 1% each in PKM-AI and PKM-GFT. These findings emphasize the importance of training in directing students' interests according to their field potentials. This training plays a strategic role in building students' competencies as young innovators ready to contribute to the development of science, technology, and social solutions. The sustainability of this program is expected to be realized through intensive monitoring and mentoring, so that the proposals generated can be implemented effectively.